2009
DOI: 10.1590/s1678-91992009000400006
|View full text |Cite
|
Sign up to set email alerts
|

Venomous snakebites and antivenom treatment according to a protocol for pediatric patients in taiwan

Abstract: and adolescents, with a median age of 9.9 years (ranging from 2 to 18 years), was identified.Forty-five patients (82%) were bitten between May and September. Thirty-five patients (64%) received antivenom therapy, 28 of them (80%) within two hours after being bitten. No fatalities occurred and only five of 35 patients (14%) had major morbidity when treated according to the protocol. Thirty-one snakes (56%) were identified and 12 of them (38%) were Naja atra. This study indicates that a protocol for children aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
5
7
2
1
Order By: Relevance
“…We bring a result of retrospectively collected data on clinical profile of snake bites in children from central [12][13][14][15][16]. Incidence was more in boys (58.75%) as compared to girls (41.25%) this is in accordance with other studies where high incidence is reported in male children which can be attributed to their behavior and nature to playmore outdoor games [17][18][19].…”
Section: Discussionsupporting
confidence: 74%
“…We bring a result of retrospectively collected data on clinical profile of snake bites in children from central [12][13][14][15][16]. Incidence was more in boys (58.75%) as compared to girls (41.25%) this is in accordance with other studies where high incidence is reported in male children which can be attributed to their behavior and nature to playmore outdoor games [17][18][19].…”
Section: Discussionsupporting
confidence: 74%
“…11 The TPCC guideline for treatment of snakebites patients only briefly described the symptomatic approach to diagnosing the culprit snake and then use of the correct antivenoms. 12 The usage of the FH antivenom is recommend as 1 vial antivenom to treat green habu (Viridovipera stejnegeri) bitten patients and 1e4 vials to treat the Taiwan habu (Protobothrops mucrosquamatus) bitten patients; while from six to 10 vials FN antivenoms were recommend to treat the Chinese cobra (Naja atra) bitten patients, and 1e4 vials to treat the Taiwan banded krait (Bungarus multicinctus) bitten patients. However, there is no clinical symptom severity grading systems described to guide the first antivenom dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations are reported in Indian and world literature. 16,17 In present study, 59.57% patients were primarily treated by medical personnel, 26.70% by paramedical people and 12.70% by tantric. Death of 6 patients in our study was due to delay in seeking primary treatment as these cases resorted to tantric measures or paramedical people for their treatment leading to delay in hospitalization.…”
Section: Discussionmentioning
confidence: 48%